Factores y relaciones que afectan la incorporación de tecnologías de información y comunicación en la educación superíor - Ortiz Medina, Pedro Martín (2009)
This study seeks to explore the factors and relationships that affect the effective inclusion of Information and Communications Technologies (ICT) in the classroom at the Higher Education level; in particular in those professors from universities linked to the Ecuadorian Consortium for the Development of Advanced Internet-CEDIA. The study is divided in two phases. First phase is focused on creating a baseline in relation to the available infrastructure and ICT uses in the Universities; explore the kind of training followed by professors in the inclusion of ICT in the classroom and the policies promoted at the institutional level about ICT in educational processes. The second part of the study is focused on understanding what influences the professors in adopting technologies. The level of knowing about technology and the level of technological innovativeness that professors show resulted to be important factors and totally linked to the individual. The paper concludes that the decision takers should take especial attention to the training their teachers receive in the use of technologies, because this is the strongest factor to predict the adoption of ICT.